A case of synchronous double cancers consisting of maxillary gingival carcinoma and intraductal papillary mucinous carcinoma, invasive: case report - Ryosuke Iwama; Hitoshi Miyashita; Atsumu Koketsu; Kiyoshi Kume; Fumiyoshi Fujishima; Atsushi Masamune; Tetsu Takahashi (BMC Oral Health, 2023)
Abstract Background The development of synchronous multiple primary cancers is one of the major causes of death in patients with head and neck cancer. Herein, we report a case of synchronous intraductal papillary mucinous carcinoma (IPMC), invasive in a patient with maxillary gingival carcinoma. Case presentation A 73-year-old female visited our hospital complaining of a mass on the left side of the maxillary gingiva. Intraorally, an exophytic tumor, 50 × 25 mm in size, was found on the gingiva of the left maxillary posterior, and a diagnosis of squamous cell carcinoma was revealed by cytology. Emission tomography/ computed tomography with 18 Fluorodeoxyglucose-Positron (18FDG- PET/ CT) showed increased accumulation in the left maxillary gingiva, the left side of cervical lymph nodes, and the main pancreatic duct. The pancreatic ductal tumor was performed the biopsy at esophagogastroduodenoscopy (EGD) and resulted in a pathological diagnosis of IPMC, invasive. The patient was diagnosed as synchronous double primary cancers consisting of maxillary gingival carcinoma cT4aN2bM0 and IPMC, invasive cT3N0M0. She refused radical treatment, and died 11 months later. Conclusion 18FDG- PET/ CT, EGD and multidisciplinary approach is required for the detection and determining the treatment strategy of synchronous double primary cancers.